2013
DOI: 10.1108/ijcthr-04-2013-0022
|View full text |Cite
|
Sign up to set email alerts
|

Festivals, special events, and the “rising tide”

Abstract: PurposeThe accurate measure of the economic contribution of festivals and special events is a challenge. Using a case study, the purpose of this paper is to demonstrate a previously un‐captured economic contribution from increased hotel rates during the period of festival or event; the “rising tide” effect.Design/methodology/approachThis paper uses a case study on Charleston's hotel occupancy changes, and how the changes coincide with the occurrence of festivals and events in the community, to demonstrate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 3 publications
(5 reference statements)
0
28
0
1
Order By: Relevance
“…Additionally, negative impacts of festivals have been understated by a focus on short‐term, rather than long‐term, impacts (Litvin et al . ). Thus, calls have been made for the measurement of broader cultural and social impacts (Van Winkle and Woosnam ) and for the refinement of exisiting measurement scales through further empirical testing (Woosnam et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, negative impacts of festivals have been understated by a focus on short‐term, rather than long‐term, impacts (Litvin et al . ). Thus, calls have been made for the measurement of broader cultural and social impacts (Van Winkle and Woosnam ) and for the refinement of exisiting measurement scales through further empirical testing (Woosnam et al .…”
Section: Discussionmentioning
confidence: 97%
“…Further critiques include claims that the focus is often on short‐term over long‐term impacts and that multiplier effects do not consider costs or distribution of gains or the extent to which the area might be better off without the festival (Felsenstein and Fleischer ; Litvin et al . ).…”
Section: Understanding Festivals: the Evidencementioning
confidence: 97%
“…Though not a new phenomenon, destinations are increasingly exploiting and promoting local culture though events and festivals, primarily to increase the contribution of tourism to the local economy. For example, Litvin, Pan, and Smith (2013) found that higher accommodation prices during festivals in Charleston provided a significant boost to the local economy while cultural events are an effective means of lengthening the tourist season, such as Easter festivities in Sardinia (Giudici, Melis, Dessì, & Ramos, 2013). Other benefits may also accrue from cultural events; For example, Houghton (2001) found that wine festivals in Victoria resulted in additional revenue and winery recognition, enhanced region awareness and community harmony, new customers for the community, and positive future visitation intentions.…”
Section: Christou Sharpley and Farmakimentioning
confidence: 99%
“…In addition, the client wants to avoid unsafe situations, discomfort, doubts, worries, constraints, make complex decisions, be treated in an undifferentiated way or feel like a nuisance or an invader (Yeoman et al, 2004). Litvin et al (2013) warn of the dangers of over-reliance on events organized by the public authorities and consequent ignorance of the development of a permanent base of tourist attractions such as corporate events. Silva (2005) mentions that it is not only the government's responsibility to create and promote events.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…The hotels that organize them are benefited in a variety of ways, either by cultivating their profile, by reinforcing the brand position (Drake, 2013) or simply by their ability to attract more customers (Crompton, 2006;Litvin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%